Evolution of the structure and properties of mechanochemically synthesized pyrrolidine incorporated manganese bromide powders. Issue 19 (15th April 2020) - Peng, Hui; Zou, Bingsuo; Guo, Yongchang; Xiao, Yonghao; Zhi, Ruonan; Fan, Xiaoyue; Zou, Min; Wang, Jianping
Abstract : Pb-free perovskite materials, C8 H20 N2 MnBr4 and C4 H10 NMnBr3 with high luminescence yields, were obtained via a simple mechanochemical process. Abstract : Due to the effects of electron correlation and spin–spin coupling, pure transition metal compounds rarely produce luminescence and ferromagnetism. In this work, the Pb-free perovskite materials, C8 H20 N2 MnBr4 and C4 H10 NMnBr3 with high luminescence yields, were obtained via a simple mechanochemical process. In C8 H20 N2 MnBr4 powders, MnBr4 2− coordinated with two pyrrolidine molecules to form an independent mononuclear structure in a crystal, with paramagnetic properties and a strong emission band at 520 nm due to the lowest d–d crystal field radiation transition for individual Mn(ii ) ions. In C4 H10 NMnBr3 powders, MnX6 4− octahedra, coordinated with a much smaller amount of pyrrolidine molecules than that in C8 H20 N2 MnBr4, formed edge-sharing linear chains of Mn-ion octahedra with a much smaller Mn–Mn distance, which produced emission bands at 628 nm due to the ferromagnetic coupling of Mn pairs or clusters. Influenced by the modification in the local crystal structure by incorporated pyrrolidine molecules, the microcrystals in these two powders exhibited different phase transition temperatures and varied lifetimes in their photoluminescence besides their emission colors. By controlling the processing time of mechanochemical reactions and pyrrolidine amount, the pyrrolidine insertion into the lattice of this transition metal halide can be adjusted to be completely realized, which provides a very simple way to change the ligand from a halide ion to an organic molecule, which regulates the Mn–Mn distance in the lattice, modifying the electronic correlation and spin coupling, thereby obtaining new manganese perovskite compounds with both strong luminescence and clear ferromagnetic properties.